(untitled) (Journal of Pathology of Nepal, 2015)
Endometrial stromal tumors are rare uterine malignancies composed of cells resembling those of proliferative endometrial stroma. Because of their indistinct clinical and radiological features, these malignancies are very rarely diagnosed preoperatively. They are mostly often diagnosed as fibroid uteruspreoperatively and as a result managed conservatively many a time. Usually distinguishing these tumors from benign smooth muscle tumors of the uterus are not problematic by light microscopy, however, difficulties arise in distinction between highly cellular leiomyomas and endometrial stromal sarcomas with smooth muscle differentiation. Here we present four consecutive cases of low grade endometrial stromal sarcomaswith emphasis on their clinical, histopathological and immunohistochemical features. By this study, we have attempted to document the histologic features of LGESS with discussion of the differential diagnoses to contribute to this rare spectrum of uterine neoplasms. Journal of Pathology of Nepal (2015) Vol. 5, 774-777